1999
DOI: 10.1007/s004050050145
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting recovery of mastoid aeration after ear surgery

Abstract: Fifty-six patients after tympanomastoid surgery were examined to determine recovery of mastoid aeration and various pre- and intraoperative factors such as eustachian tube (ET) function, how the mastoid mucosa had been treated during surgery and whether or not a large silastic sheet had been placed in the middle ear or a ventilation tube used. Mastoid aeration recovery was confirmed by computed tomography in 27 of the 57 cases (47%) within 12 months of surgery. Among the factors examined, preservation of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…Thus, tympanoplasty and mastoidectomy alone are an imperfect therapy for the treatment of intractable otitis media because they result in the absence of a mastoid air cell system, thereby precluding function. The operated ear is still left with the innate cause of the cholesteatoma or the adhesive otitis media, as well as the pathophysiologic background and therefore the tendency to develop a negative gas balance in the middle ear 9 . When traditional surgical techniques are performed on ears for intractable otitis media, the postoperative course is complicated by an atelectatic condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, tympanoplasty and mastoidectomy alone are an imperfect therapy for the treatment of intractable otitis media because they result in the absence of a mastoid air cell system, thereby precluding function. The operated ear is still left with the innate cause of the cholesteatoma or the adhesive otitis media, as well as the pathophysiologic background and therefore the tendency to develop a negative gas balance in the middle ear 9 . When traditional surgical techniques are performed on ears for intractable otitis media, the postoperative course is complicated by an atelectatic condition.…”
Section: Discussionmentioning
confidence: 99%
“…1). As mentioned above, the failure of pressure regulation in the middle ear is thought to be a possible concern in cases of incurable otitis media 3,8,9 …”
Section: Introductionmentioning
confidence: 99%
“…Restoration of aeration in the tympanic cavity after surgery appears to depend upon whether or not air comes into the tympanic cavity through the adjacent Eustachian tube [17]. The patency of Eustachian tube is obtained from normal condition of middle ear mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…A hypothetical comparison between those traditional procedures and the present endoscopic surgical procedure in improving postoperative ventilation to epitympanum and mastoid antrum shows that the present endoscopic procedure is less invasive and more mucosal epithelium preservative then those conventional procedures. Study of Tanabe et al showed that preservation of mastoid mucosa played vital role in recovery of mastoid aeration after surgery 7 .…”
Section: Discussionmentioning
confidence: 99%